THE CHARACTERISTICS OF MALAYSIAN DIETITIANS WHO INQUIRE ABOUT PATIENTS’ SPIRITUAL NEEDS - Aflah Afandi; Mohamad, Hasbullah; Mamat, Nik Mazlan (International Journal of Allied Health Sciences, 2019)
Many dietitians do include spiritual approach in their conversations during dietary counselling, particularly in helping patients coping with the burden of long-term illness. It seems to be an exceptional task for them as they had no formal training to perform patients’ spiritual needs inquiries. While this has become a normal practice among Malaysian dietitians, the evidence from the current literature is very limited. Thus, we aimed to describe the characteristics of dietitians who have ever inquired about patients’ spiritual needs during dietary counselling. Following several announcements made in official Facebook closed-group for Malaysian Dietitians’ Association, and Malaysian Nutrition/Dietetics Graduates, data was gathered using on-line survey through an established web host since May 2019. We used descriptive analysis and chi-square test to distinguish further the characteristics between dietitians graduated from IIUM and other local institutions. Out of eighty-nine dietitians who participated in this survey, almost 60% (n=53) of them have ever made such an inquiry in which nearly two-thirds of them are IIUM graduates (64.2%, n=34), and working with less than ten years of experience. Overall, the characteristics of dietitians who graduated from IIUM and non-IIUM are almost similar. Majority of them work with the government and have a high interest in diabetes and weight management cases. The findings show that they agreed that religion/spirituality do influence patients’ health and the healing process. They feel comfortable and appropriate to talk about it when patients brought it up and open to share their religious belief or experience with patients when necessary. The trends of making such inquiries are increasing with years of experience. However, non-IIUM graduate dietitians would prefer to pray (make Du’a) with a patient only when the patient asks (26%, p=0.035). In conclusion, the willingness to discuss the patient’s spiritual needs among dietitian is possibly developed through experience, regardless of where they graduated from.